I Know That You Know That I Know : Narrating Subjects from Moll Flanders to Marnie - Butte, George, 1947- (Book collections on Project MUSE., 2004)
"In I Know That You Know That I Know, Butte explores how stories narrate human consciousness. Butte locates a historical shift in the representation of webs of consciousnesses in narrative - what he calls "deep intersubjectivity"--And examines the effect that shift has since had on Western literature and culture. The author studies narrative practices in two ways: one pairing eighteenth- and nineteenth-century British novels (Moll Flanders and Great Expectations, for example), and the other studying genre practices - comedy, anti-comedy and masquerade - in written and film narrative (Jane Austen and His Girl Friday, for example, and Hitchcock's Cary Grant films)."--Jacket.